The Influence of Celebrity Endorser and Attitudes on Advertising towrads Attitudes on Brand and Repurchase Intention - Mukti Aji, Lintang Pamugar (Universitas Pendidikan Ganesha, 2018)
The purpose of this research was to analyze the effect of celebrity endorser and attitude toward advertising on attitude toward brand and repurchase intention. This research used design explanatory. Population were IM3 prepaid card customers in Surakarta. The sampling technique was convenience sampling with 100 respondents. Techniques of data collection used observation, documentation, questionnaires and literature study. Analysis used validity test, reliability test, t-test, f-test, R Square test and path analysis. The results showed that celebrity endorser significant affected on attitude toward brand. Attitude toward advertising significant affected on attitude toward brand. Celebrity endorser significant affected on repurchase intention. Attitude toward advertising significant affected on repurchase intention. Attitude toward brand significant affected on repurchase intention. Celebrity endorser and attitude toward advertising affected on attitude toward brand simultaneous. Celebrity endorser, attitude toward advertising and attitude toward brand affected on repurchase intention simultaneous. The coefficient of determination of total results (R2) was 59,0% so repurchase intention can be explained variable celebrity endorser, attitude toward brand within attitude toward brand as a intervening variables and the remaining 41.0% was explained variables outside the model. Celebrity endorser is a proven direct and indirect effect on repurchase intention.